The Impact of Purpose-Driven Organisation and Organisational Change Capability to the Performance of Muhammadiyah Hospitals in the Pandemic Era - Fauzi, Indra Nur; Suhariadi, Fendy; Eka , Albertus (Journal of Ecohumanism, 2024)
Organizational performance might indirectly be impacted by the variable of purpose-driven organization (PDO). Mourkogiannis (2014) defines organisational purposes as a set of values and beliefs that defines the organisation, the purpose inspires and motivates the organisation's employees, too. This purpose also becomes a reason for doing or creating things. Muhammadiyah hospitals have determined their purpose as inclusive health services and it is strongly reflected in the message of Muhammadiyah founding father, KH Ahmad Dahlan. When inaugurating the PKO Muhammadiyah Clinic in Yogyakarta in 1923, he said that: "the purpose of PKO is to help everyone in sorrows by using the principles of Islam, not by dividing the nation and religion" (Thohari, 2021). Purpose-orientation means having purposes or concrete objectives for the benefit of all communities by providing wider services, which is beyond its financial performances (Henderson, 2019). This study has the objectives to confirm a few previous study results on Organizational Performance (OP) and the organisation's change capability (OCC) as the mediating variable. This study employs quantitative data analysis using Structural Equation Model (SEM). This study addresses three hypotheses. Hypothesis 1 of the study is proved that improving PDO will lead to an improvement in OCC by 0.945. Hypothesis 2 of the study has confirmed that improvement in OCC improves OP by 0.795. Hypothesis 2 of the study proves that OCC has a positive impact on OP. Meanwhile, hypothesis 3 is proved that there is a structural relationship between PDO and OP in a form of indirect impact to OCC as mediating variable. This study differs from previous studies as the study: 1) determines the objects are Muhammadiyah Hospitals which applies the social entrepreneurship organisation (SEO) ownership model and OCC; 2) the study period is set during the COVID-19 pandemic which significantly impacts the healthcare industry.